TRANSITION FROM CARBONATE PLATFORM TO PELAGIC DEPOSITION (MID JURASSIC- LATE CRETACEOUS), VOURINOS MASSIF, NORTHERN GREECE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
A Jurassic- Cretaceous carbonate succession crops out along the Zyghosti Rema, Kozani (Northern Greece). The substratum consists of the ophiolitic succession of the Vourinos Massif (Pelagonian Domain): serpentinites tectonically overlain by basalts, with thin lenses of radiolarian cherts of middle Bathonian age. The contact with the overlying Jurassic limestones is tectonic. Eight informal units have been distinguished within the Mesozoic limestones, from the base upwards. (A) bioclastic, intraclastic and oolitic packstone (Callovian- Oxfordian). (B) bioclastic packstone and coral boundstone (Oxfordian ). (C) bioclastic and oncoidal wackestone with Clypeina jurassica (Oxfordian- Upper Kimmeridgian). (D) (Upper Kimmeridgian- Portlandian): oncoidal packstone and rudstone (facies D1); intraclastic and bioclastic grainstone and packstone (facies D2); neptunian dykes with intraclastic and bioclastic wackestone and packstone filling (facies D3); neptunian dykes with Fe-Mn rich laterite filling and with pink silty filling of early Late Cretaceous age. An unconformity surface, due to emersion and erosion of the platform during the latest Jurassic- Early Cretaceous, is overlain by (E) intraclastic, bioclastic packstone and grainstone (Cenomanian). (F) massive body of debrites with coral, echinoderm, algae and rudist large clasts (facies F1) (Cenomanian); turbiditic beds of bioclastic, intraclastic and lithoclastic rudstone and grainstone (facies F2). (G) thin bedded bioclastic mudstone and wackestone with planktonic foraminifers and radiolarians, alternating with turbiditic beds of bioclastic, intraclastic packstone and rudstone and with conglomeratic levels and slumped beds of the previous turbidites (upper Santonian- lower Campanian). (H): bioclastic packstone with planktonic foraminifers (facies H1) (lower Campanian - ?Maastrichtian); amalgamated turbiditic beds of bioclastic wackestone and packstone with planktonic foraminifers (facies H2); turbiditic beds of bioclastic packstone and rudstone (facies H3). These features allow to recognise the following sequence of events: 1) development of a carbonate platform in the Middle and Late Jurassic; 2) its overthrusting onto the ophiolites and its emersion starting from latest Jurassic time, with erosion and deposition of laterites; 3) marine transgression on the Jurassic platform and on the ophiolites during the early Late Cretaceous, and 4) extensional tectonism and platform demise starting in the Cenomanian, with sedimentation of gravity flows and turbidity currents deposits from the Cenomanian to the Campanian- ?Maastrichtian.